IN THE SEARCH FOR MECHANISMS OF SELF-ACTUALIZATION AND ACTIVITY OF STUDENTS: THE ANTHROPIC PRINCIPLE TECHNOLOGY EDUCATION - S. V. Dmitriev; S. D. Neverkovich; D. I. Voronin; E. V. Bystritskaya (Вестник Мининского университета, 2017)
At the present stage of development of education is clearly detected the movement of various social and humanitarian disciplines to interdisciplinary and Meta-study. The article is an attempt, based on an interdisciplinary approach to analyze the anthropic principles of educational technology. For the authors of the proposed theoretical and methodological basis of identified and described the basic components of the structuring of educational space and didactic methods of modeling specific professional activity in the sphere of physical culture. The article describes the principles developed by us anthropic technologies. Especially stresses the need and importance of nature conservation kulturotvoryaschego educational system and provide a subject position of students in the educational space of the university. In the latter case, a special place is given to reflexive stages of self-reflection and self-transformation of the creative person in the professional culture - the identification of "I" self-actualization "I" self-realization "I am."